Impact of innovativeness on business performance in Croatian companies - Helena Šlogar (Ekonomski Vjesnik, 2020)
The purpose of the research was to examine the relationship between innovativeness and business performance in Croatian export companies. The research involved 303 Croatian companies from the fields of manufacturing industry and information and communication technology. The research was conducted through a survey method during the last three months of 2016. The sampling method used for the purpose of this research was stratified random sampling, while regression analysis was used for data analysis. The structure of correlation between individual responses and individual groups of responses was analysed by canonical analysis and cluster analysis. The results show that there is a positive relationship between innovativeness and business performance in Croatian companies. The research has practical implications for Croatian companies in the ability to increase their efficiency and innovativeness. The empirical contribution was achieved by defining the direction and impact of innovativeness on business performance. The results offer theoretical and managerial implications. In the context of this research, it is likely that innovativeness and business performance influence a company’s innovative activities, which can be positively reflected in creating and maintaining the competitive advantage on the market.